Islamic Religious Education through Habituation of Religious of Indonesian Muslim Children in Korea, Before and During the Covid-19 Pandemic - Sonezza Ladyanna; Kim Jang Gyem (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2022)
The Covid-19 pandemic significantly impacted various aspects of life, including education and religious rituals in minority areas. This article compares the habituation of religious teachings to Indonesian Muslim children in Korea before and during the Covid-19 pandemic. This research was conducted using qualitative methods to examine religious education and its relevance to people's lives. The research subjects were Indonesian Muslim families in Korea with school-aged children who attended Korean public schools. The object of research is religious habituation to religion before and during the Covid-19 pandemic in 2020-2021. The results showed an increase in the quantity and quality of habituation of religious teachings in Muslim children from Indonesia living in Korea. This increase was obtained from a comparison before and during the Covid-19 pandemic. This is due to the home school policy, social restrictions, and the ban on feeding at school during the Covid-19 pandemic